The Development of English Vocabulary Reading Skills by Using Video Teaching Aids for Pratomsuksa 1 Students - Samaisani, Anchaliporn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The research aims to: 1. compare students’ English vocabulary reading-aloud skills before and after learning through video-assisted teaching; and 2. compare the reading skills of the students who were taught through the video-assisted teaching method and those who were taught by the normal teaching method. The samples were Prathom Suksa 1 students from two classes at Ruam-Numjai Center School, recruited by cluster random sampling. The research instruments were: 1) ten lesson plans of video-assisted teaching; 2) ten lesson plans of the normal teaching method; 3) four sets of video-assisted teaching; and 4) an English vocabulary reading-aloud test with 20 items. The statistics used to analyze the data included mean, standard deviation, and percentage. The t-test independent with a rating scale was used to analyze the students’ average score after the learning, and the t-test dependent was used to analyze their average score both before and after the learning. The results showed that: 1. after the learning, the students who were taught through the video-assisted teaching method gained improvement in their English vocabulary reading-aloud skills with a statistical significance of .05 (t=11.99, df=25, Sig=.000); and 2. the students who were taught by the video-assisted teaching method had higher English vocabulary reading-aloud skills than the students who were taught by the normal teaching method with a statistical significance of .05 (t=1.97, df=50, Sig=.027).